(untitled) (Bangladesh Journal of Bioethics, 2021)
The use of human subjects in research comes with lots of ethical challenges. The purpose of this review is to assess the various ethical issues that have been associated with biomedical research in Nigeria. This article also finds out the possible ways of improvement of this scenario. Pubmed/Medline, Google Scholar, JSTOR, and AJOL search were the possible search engine for literature from 2000 to 2020. Key words were used including, ethical issues, biomedical research and Nigeria. Of the 113 publications were found., A total of 18(15.9%) articles fulfilled the study inclusion criteria and were included in this review. Twelve ethical issues were highlighted including Informed consent (12 studies), autonomy and voluntariness (8 studies), beneficence (8 studies), counseling (5 studies), compensation (4 studies), professional behavior and attitudes (2 studies), confidentiality (2 studies), social, cultural and religious practices (2 studies), scientific integrity (1 study), communitarianism (1 study), equity (1 study), and trust (1 study). We found that there are ethical issues in biomedical research in Nigeria of which informed consent is most widely studied. Also, participants had varying degree of understanding of their rights as research subjects. As a result, there is need to enhance the capacity of investigators to better understand these issues and also increase their explanatory skill to help participants achieve complete understanding of their various rights and process.